Water deficit on the growth and yield of irrigated soybean in the Brazilian Cerrado region - Elvis da S. Alves; Lineu N. Rodrigues; Rubens A. de Oliveira; Douglas R. Lorena (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The increase in disputes over water use in the Brazilian Cerrado has demanded improvements in irrigation management and increase in water use productivity. In this context, deficit irrigation is an interesting management strategy, as it enables water savings without significant losses of yield. The present study aimed to evaluate the phenology and yield of a soybean cultivar subjected to different soil moisture contents. The experimental design used was randomized blocks with five treatments and four replicates. In each treatment, an irrigation strategy was applied based on the available water in the soil (AW). The T1 treatment was performed by applying from 80 to 100% AW; in T2 treatment, the allowed variation was from 60 to 80% AW; in T3 treatment, it was from 40 to 60% AW; in T4, from 20 to 40% AW; and in T5, from 0 to 20% AW. It was verified that, in winter and summer, even without the need to reduce water withdrawal, it is recommended to apply from 60 to 80% of the available water in the soil for soybean crop, without decreasing yield. In situations of water restriction, it is possible to have yield of around 55 and 70% in winter and summer, respectively, for the condition from 20 to 40% of the available water in the soil.